On the spectral theory of a Generalized Differential Krein System - Sakhnovich, L. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We consider the generalized differential Krein system. We establish the relationship between the behavior of a solution of the system and the character of the corresponding spectral matrix function.